Ruminant cluster CD41/CD61 - Mateo, A.; Pintado, C.O.; Lastra, J.de la; Dusinsky, R.; Simon, M.; Naessens, Jan; Llanes, D. (Elsevier, 1996)
After analysis of flowcytometry data on bovine and ovine cells and immunoprecipitation studies, a cluster of seven MAbs-CAPP2 (3W-232), IL-A164 (M430), IL-A166 (3W-226), IVA30 (3W-069), IVA31 (3W-468), IVA38 (3W-349) and IVA125 (3W 528) - was shown to detect bovine and ovine CD41/Cd61 (also known as alpha IIb beta 3 integrin and GpIIb/IIIa). One additional MAb from the workshop panel, Co-20A1 (3W-386), was shown to react with the ovine GpIIb/IIIa molecule only (Pintado et al., 1995; Mateo et al., 1996a). MAb Co-35E4, not submitted to the workshop, also precipitated the platelet integrin and cross-reacted with several species (Pintado et al., 1995)